Survey frequency of the depression and anxiety levels of infertile women in western Iran (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND Infertility among couples is a painful emotional problem, which results in the feeling of grief in the form of psychological problems such as depression and anxiety. The present study was aimed to survey the frequency of depression and anxiety levels of infertile women in western Iran in 2017. METHODS This cross-sectional study used a simple random sampling method for selecting the sample. The study population consisted of all infertile women who went to Farhangian health center in Ilam. The Beck’s Depression Inventory, Beck’s Anxiety Inventory, and demographic characteristics questionnaire were used for collecting the data. The questionnaires were distributed among midwife experts and patients. The collected data were analyzed by the chi-square test and variance analysis using SPSS version 20. RESULTS Among 200 infertile women, 53.5%, 32%, 11%, and 3.5% suffered from severe, moderate, mild, and no anxiety, respectively. However, 96.5% suffered from various degrees of anxiety with 85.5% from clinical anxiety. In addition, 42%, 19.5%, 14.5%, and 24% suffered from severe, moderate, mild, and no depression, respectively. However, 76% suffered from various degrees of depression with 61.5% from clinical depression. There is a significant relationship between the education level of husbands, education level of women, and type of infertility (p<0.05). Women who had a lower than diploma education level and primary infertility suffered from higher anxiety levels. CONCLUSIONS There was a high level of anxiety and depression in infertile women; therefore, it is necessary to pay attention to these disorders in the process of treatment of infertile women.